2013
DOI: 10.1111/ecot.12017
|View full text |Cite
|
Sign up to set email alerts
|

Shocks and rigidities as determinants of CEE labour markets’ performance

Abstract: In this article, the impact of real wage, productivity, labour demand and supply shocks on eight Central and Eastern European (CEE) economies from 1996–2007 is analysed with a panel structural vector error correction model. A set of long‐run restrictions derived from the dynamic stochastic general equilibrium (DSGE) model is used to identify structural shocks, and fluctuations in foreign demand are controlled for. We find that the propagation of shocks on CEE labour markets resembles that found for OECD countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…By using stationarity tests they found that the unit root hypothesis could be rejected after controlling for structural changes and business cycle effects. (Bukowski et al, 2013) investigated the impact of shocks and the rigidities of the labour market in Central and Eastern European transition countries and concluded that the labour demand shocks were the main determinant of unemployment variability in the short run, but also found the wage rigidities being very important factors.…”
Section: A Review Of Previous Researchmentioning
confidence: 99%
“…By using stationarity tests they found that the unit root hypothesis could be rejected after controlling for structural changes and business cycle effects. (Bukowski et al, 2013) investigated the impact of shocks and the rigidities of the labour market in Central and Eastern European transition countries and concluded that the labour demand shocks were the main determinant of unemployment variability in the short run, but also found the wage rigidities being very important factors.…”
Section: A Review Of Previous Researchmentioning
confidence: 99%
“…Such questions have been mainly studied econometrically by, e.g. Layard et al (1991), Blanchard and Wolfers (2000), Nickell et al (2005), Bassanini and Duval (2006), Bukowski et al (2013), while DSGE applications have been rare. Our approach follows, e.g.…”
Section: Introductionmentioning
confidence: 99%